The Effect of Work-Life Balance, Work Environment, and Work Discipline on Employee Performance in AKPRIND University Employees - Hidaya, Vera Nurul; Dwiarti, Rina (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this research is to ascertain how employee performance is affected by work-life balance, work environment, and work discipline. AKPRIND University was the site of this study. This study uses SPSS software and is quantitative in nature. Direct distribution of questionnaires and observation are two methods and instruments used in data collecting. There were 104 responders in the study's sample. The study's findings suggest that neither work-life balance nor the workplace environment significantly improves AKPRIND University workers' performance. Employee performance at AKPRIND University is positively and significantly impacted by work discipline.